THE RELATIONSHIP OF KNOWLEDGE AND FAMILY SUPPORT TO MOTHERS WITH EXCLUSIVE BREAST FEEDING AT THE PAMATANG SILIMAHUTA HEALTH CENTER SIMALUNGUN DISTRICT - Nurmala (PT. Radja Intercontinental Publishing, 2021)
Based on the 2013 Basic Health Research (Riskesdas) data, it shows that breastfeeding in Indonesia is currently still a cause for concern, only 53.4%. Data from health professionals achieving exclusive breastfeeding at Pamatang Silimahuta Health Center in 2016 was 64%. To find out the relationship between Knowledge and Family Support for Mothers with Exclusive Breastfeeding at the Pamatang Silimahuta Health Center in 2017. The research method used this type of analytic survey research with a cross-sectional approach to 75 breastfeeding mothers who had babies aged 7-24 months in the Pamatang Silimahuta Health Center area. The sampling technique uses the Notoatmodjo formula (2005). Data analysis used the chi sguare test. The results showed that p-0.063 and p0.098 (a0.05) were obtained so that Ha was rejected and Ho was accepted.